Anti-Candidal Activity And Toxicity Studies Of Alginate-Enclosed Chitosan–Calcium Phosphate-Loaded Fe-Bovine Lactoferrin Nanocapsules - Khoo, Miew Leng (2018)
Lactoferrin has been known to have antimicrobial properties. This research was conducted to investigate the anti-candidal activity and toxicity of Alginate/EUDRAGIT® S 100-enclosed chitosan–calcium phosphate-loaded Fe-bLf nanocapsules (NCs) by in vitro and in vivo study. The screening of NCs for antimicrobial activity showed that NCs has good anti-candidal activity. The minimum inhibitory concentration (MIC) value of NCs using broth microdilution method was found to be 500 μg/mL. The growth profile study demonstrated that the NCs at MIC, two times MIC and four times MIC inhibited the growth of Candida albicans USM-K1 (C. albicans). The electron microscopy studies showed that NCs caused the destruction of yeast cells by disruption of cell wall and cell membrane with increase of incubation time until 36 hours.